Regulation of α-Synuclein Expression by Poly (ADP Ribose) Polymerase-1 (PARP-1) Binding to the NACP-Rep1 Polymorphic Site Upstream of the SNCA Gene - Chiba-Falek, Ornit (The American Society of Human Genetics, 2005)
Alleles at NACP-Rep1, the polymorphic microsatellite repeat located ∼10 kb upstream of the α-synuclein gene (SNCA), are associated, in some reports, with differing risks of sporadic Parkinson disease (PD). We showed previously that NACP-Rep1 acts as a negative modulator of SNCA transcription, with an effect that varied threefold among different NACP-Rep1 alleles. Given that duplications and triplications of SNCA have been implicated in familial Parkinson disease (PD), even a 1.5–2-fold increase in α-synuclein expression may, over many decades, contribute to PD. Thus, the association of different NACP-Rep1 alleles with PD may be a consequence of polymorphic differences in transcriptional regulation of SNCA. Here we aimed to identify the factor(s) that bind to NACP-Rep1 and potentially contribute to SNCA transcriptional modulation, by pulling down proteins that bind to NACP-Rep1 and identifying them by mass spectrometry. One of these proteins was poly-(ADP-ribose) transferase/polymerase-1 (PARP-1), a DNA-binding protein and transcriptional regulator. Electrophoresis mobility shift and chromatin immunoprecipitation assays showed specific binding of PARP-1 to NACP-Rep1. Inhibition of PARP-1’s catalytic domain increased the endogenous SNCA mRNA levels in cultured SH-SY5Y cells. Furthermore, PARP-1 binding to NACP-Rep1 specifically reduced the transcriptional activity of the SNCA promoter/enhancer in luciferase reporter assays. This down-regulation effect of PARP-1 depended on NACP-Rep1 being present in the construct and was abrogated by inhibiting PARP-1’s catalytic activity with 3-aminobenzamide. The association of different NACP-Rep1 alleles with PD may be mediated, in part, by the effect of PARP-1, as well as other factors, on SNCA expression.